Combined effect of salinity and cadmium in the presence of other metals (Zn & Cu) and GSH on lysosomal responses in an arcid blood clam Anadara granosa - Anthony, K; Patel, B (Indian Journal of Fisheries, 2011)
Exposure of tropical arcid blood clam Anadara granosa to sublethal concentration of Cd, Zn, Cu and GSH (Glutathione) at different salinities (16 - 32 g kg-’) induced various changes in the activities of the lysosomal marker enzymes - arylsulphatase and acid phosphatase. Changes in the lysosomal enzyme activity on exposure either to Cd or GSH was inversely related to ambient salinity. Cu inhibited enzyme activity at both salinities. Zn, however, caused no significant changes. GSH together with Cd reduced the enzyme activity at both salinities whereas the presence of Zn or Cu significantly (P<0.001) increased it. So also Cd in combination with Zn and Cu stimulated (total and free) the arylsulphatase activity significantly (P<0.001) at lower salinity, however, at higher salinity it was not affected appreciably. GSH together with Cd, Zn and Cu ameliorated the enzyme activity within the range of control. The lysosomal bound latent activity in all the cases of Cd exposure except the one with GSH at lower salinity reduced irrespective of salinity changes. Thus at lower salinity the enzyme activity was not depended upon the levels of metals in the ambient salinity. Further the salinity and speciation of these metals played a significant role in the toxicity of Cd. Moreover, GSH in the presence of Cd, Zn and Cu subsided the toxic effect of Cd in marine water